Women's Voices in Contemporary Hasidic Communities. - Waldman, Rose (Shofar: An Interdisciplinary Journal of Jewish Studies)
One of the central features of contemporary Hasidic communities is gender segregation. Women and men operate in separate spheres, and the public sphere favors men. This is due both to halakha , Judaic law—which rules that most formal rites of traditional Orthodox Judaism be conducted by men—and the norms of modesty, which is underscored more sharply for women. Consequently, Hasidic women have limited opportunities for visibility in the public sphere of their communities. But the gender binaries aren't absolute, and compulsory interactions in the workplace and on the streets complicate the assumption that the Hasidic community operates under a clear-cut dichotomy of men in the public arena and women in the domestic sphere. In fact, Hasidic women have a place and voice in the public territories of their communities, though their voices may garner less visibility and press. Still, they insert their voices and express their intelligence and creativity in many different venues within their community's constructs. This article explores the various ways in which Hasidic women speak, and are heard, in comingled communal areas. It demonstrates how women have created a space for the expression of their intelligence and creativity within the constraints of their community's lifestyle. Through the lens of three categories—talks and lectures, media and publishing, and music and song—this article examines how much influence Hasidic women have in their own communities.